The king who refused to die: The Anunnaki and the search for immortality - Sitchin, Zecharia (Bear & Company, 2013)
""Zecharia Sitchin's secret allegorical novel that brings to life the key concepts of his bestselling book The 12th Planet"--Provided by publisher"--